PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) TERHADAP HASIL BELAJAR PASSING BAWAH BOLAVOLI STUDI PADA SISWA KELAS X TPM SMK NEGERI 2 PROBOLINGGO - ALEXANDER WAHYUDI, ROBERT (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstrac Researcher aims: 1. To know the influence of using teams games tournament (TGT)  type-cooperative learning model for If there is influence of using Teams games tournament (TGT) type-cooperative learning model for the result on volleyball under passing learning for X-garde students of SMK Negeri 2 Probolinggo. 2. To know how big is the influence for the result of learning for x-grade students SMK Negeri 2 Probolinggo. Kind of this research is experiment researce which designed one group pretest-posttest design. Population which used is students of x-gade SMK Negeri 2 Probolinggo.The result of this research can be concluded that there are significant influence of using the teams games tuornament (TGT) type-cooperative learning model for the result on volleyball under passing learning for X-garde students of SMK Negeri 2 Probolinggo. The significant inflence can be showen based on wilcoxon research result, it is Z hitung, 4,936 >Ztabel1,96 orAsymp Sig = 0,000 < 0,05. So the conclution is using of the learning model can increase the students average result of the learning volleyball underpassing, average value 13,63%. Keywords: learning model, cooperative-TGT, study result, volleyball under passing.